2008
DOI: 10.1590/s0100-204x2008000800010
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression, induced by salicylic acid and Fusarium oxysporum f. sp. lycopersici infection, in tomato

Abstract: -The objective of this work was to determine the transcript profi le of tomato plants (Lycopersicon esculentum Mill.), during Fusarium oxysporum f. sp. lycopersici infection and after foliar application of salicylic acid. The suppression subtractive hybridization (SSH) technique was used to generate a cDNA library enriched for transcripts differentially expressed. A total of 307 clones was identifi ed in two subtractive libraries, which allowed the isolation of several defense-related genes that play roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
6
0
2
Order By: Relevance
“…These data corroborate with those found in the experiment of do Amaral et al. , which suggests that the gene found in the EST subtractive library is really involved in the response to fungus inoculation, that is, it is being differentially expressed after contact with the pathogen in BHRS genotype.…”
Section: Resultssupporting
confidence: 90%
“…These data corroborate with those found in the experiment of do Amaral et al. , which suggests that the gene found in the EST subtractive library is really involved in the response to fungus inoculation, that is, it is being differentially expressed after contact with the pathogen in BHRS genotype.…”
Section: Resultssupporting
confidence: 90%
“…It is well known that β-1, 3-glucanases and chitinases act either directly by degrading the fungal cell wall or indirectly by releasing oligosaccharide elicitors of defense reactions, and thus play important roles in defence response against fungal infection. Differential expression of chitinases and β-1, 3-glucanases has been observed during compatible plant-fungal interactions in other plant-fungus interaction systems (Cheong et al 2000;Bieri et al 2003;Amaral et al 2008). Therefore, it is likely that at this stage of infection, up-regulation of pathogenesisrelated proteins genes especially chitinases and β-1, 3-glucanases indicated that a comprehensive network of defence response was activated in watermelon plants upon FON1 infection.…”
Section: Establishment Of Watermelon-fon Interaction System For Transmentioning
confidence: 98%
“…Down-regulation of the aquaporins and drought-responsive genes may contribute to the development of wilt symptoms (Dowd et al 2004;Amaral et al 2008;Sade et al 2009;Zhou and Wu 2009). At this stage, several transcription factors were significantly induced, e.g., ERF-like proteins, Myb family transcription factors, ethylene-responsive transcriptional coactivator, and RING-H 2 finger protein precursor.…”
Section: Establishment Of Watermelon-fon Interaction System For Transmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of genes has contributed to the understanding of the mechanism of modulation of microorganisms under different abiotic conditions (Amaral et al, 2008). However, transcriptional changes do not reflect the expression of proteins (Gygi et al, 1999) since post-transcriptional processes, which change the amount of active protein derived from synthesis, modification, and degradation of the protein, are not taken into consideration.…”
Section: Introductionmentioning
confidence: 99%